Statistical Analysis of the Risk Assessment of Investors’ Investments in Securities Portfolio - Milutin DOBRILOVIĆ; Dragana PETROVIĆ; Milena ILIĆ; Bojan S. RISTIĆ (Communications of International Proceedings, 2020)
The subject of the research study is the measurement of the total investment risk through the statistical measures of dispersion (variance and the standard deviation), which give the investor information on the deviation of the realized annual return from average returns when making decisions on investing in company shares on the market. However, we should bear in mind the fact that the investor also wants to know how returns on investments in the shares of different companies move together. This cannot be determined by observing risk dispersion measures. Therefore, when making a decision on investing in securities, investors also use the measures of the degree of the linear relationship between the shares, such as covariance and a correlation coefficient. The aim of the research study is to point out the fact that diversified investors strive to provide the least risky instruments in their possession on the basis of risk assessment through statistical risk assessment measures. However, the problem of assessing the risk of investing in securities is a complex concept, because it includes the interdependence of assessing the rate of return on securities and investment risk, based on which the investor considers a possible return offered individually by each observed security.
Keywords: statistical analysis; investment risk management; variance; standard deviation; diversification